Portable proton exchange membrane fuel cell using polyoxometalates as multi-functional hydrogen carrier. (1st May 2022) - Shen, Yuanting; Yan, Xiaohui; An, Liang; Shen, Shuiyun; An, Lu; Zhang, Junliang
Highlights: A portable PEMFC system is proposed and realized via using POM as hydrogen carrier. The hydrogen can be stored by POM solution at atmospheric temperature and pressure. POM is hydrogenated by multiple hydrogen sources including H2, H2 O and NaBH4. Fuel cell with air-breathing cathode displays a power density of 51.3 mW cm −2 . Abstract: Proton exchange membrane fuel cell (PEMFC) is an ideal energy-conversion technology for portable, motile as well as stationary applications. However, the use as a portable power source is still hindered by the stringent requirements for hydrogen storage. Herein, we propose a PEMFC system using hydrogenable polyoxometalate (POM) solution as hydrogen carrier that enables the whole system to work under atmospheric temperature and pressure. A proof-of-concept air-breathing PEMFC is constructed and three typical POMs are tested, the corresponding results demonstrate good cell performance and stability. Another impressive result shows that the hydrogen carrier, POMs, can be hydrogenated by multiple hydrogen sources such as H2, H2 O and NaBH4 through both electrochemical and chemical ways. The newly designed system obtained a peak power density of 51 mW cm −2, making the real-world application of portable PEMFC possible.